2017
DOI: 10.1080/10428194.2017.1287363
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B-cell lymphoma in the United States (US): a population-based study using Surveillance, Epidemiology, and End Results program and National Cancer Database*

Abstract: A population-based study of intravascular large B-cell lymphoma (IVLBCL) in the US was conducted to determine incidence, demographic and clinical characteristics, prognostic factors, and survival compared with diffuse large B-cell lymphoma not otherwise specified (DLBCL NOS). In the years 2000-2013, the age-adjusted incidence rate of IVLBCL was 0.095 (case/1,000,000). The incidence of IVLBCL increased significantly from 2000 to 2013 (annual percentage change = 9.84, p = 0.002). We identified 344 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 26 publications
3
62
0
1
Order By: Relevance
“…Despite the long study duration, all the patients with in vivo diagnosis, except one, were uniformly treated with rituximab and CHOP, although the doses of cytotoxic agents were modified according to patient condition. The 5‐year survival rate of treated patients was approximately 60%, and this value was better than the 5‐year survival rate of 46·4% from the Surveillance, Epidemiology, and End Results (SEER) database from the USA (Rajyaguru et al , ).…”
Section: Discussionmentioning
confidence: 83%
“…Despite the long study duration, all the patients with in vivo diagnosis, except one, were uniformly treated with rituximab and CHOP, although the doses of cytotoxic agents were modified according to patient condition. The 5‐year survival rate of treated patients was approximately 60%, and this value was better than the 5‐year survival rate of 46·4% from the Surveillance, Epidemiology, and End Results (SEER) database from the USA (Rajyaguru et al , ).…”
Section: Discussionmentioning
confidence: 83%
“…The current treatment approach in most cases is the CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) regimen similar to the patients with diffuse large B cell lymphoma, not otherwise specified (DLBCL, NOS). With the introduction of rituximab‐based chemotherapeutic regimens, the outcome of IVLBCL has substantially improved, with an overall 5‐year survival rate similar to that of DLBCL, NOS …”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of rituximabbased chemotherapeutic regimens, the outcome of IVLBCL has substantially improved, 7,8 with an overall 5-year survival rate similar to that of DLBCL, NOS. 9 Recently, immune check-point inhibitors have shown promising results in various solid, as well as some lymphoid, malignancies, particularly classic Hodgkin lymphoma. Preliminary results from an ongoing Phase Ib trial have shown that combination of anti-programmed cell death ligand 1 (PD-L1) (atezolizumab) with obinotuzumab (type II glycoengineered anti-CD20 monoclonal antibody) is well tolerated and has anti-tumour activity in previously heavily treated relapsed refractory non-Hodgkin lymphoma (NHL) cases, including DLBCL.…”
mentioning
confidence: 99%
“…Emerging work has demonstrated that with timely treatment, particularly with the addition of CD20‐directed therapy, outcomes may be more similar to those seen in diffuse large B‐cell lymphoma (DLBCL) than historically anticipated. Indeed, a recent United States registry study demonstrated that patients with IVLBCL had survival outcomes comparable to DLBCL‐not otherwise specified (NOS) in the rituximab era although specific clinical, pathological, and treatment data were unavailable given the nature of the analysis (Rajyaguru et al , ). In order to gain further insight into the prognosis of IVLBCL and its management, we report on a multicentre, retrospective review of 54 IVLBCL patients diagnosed across nine academic medical centres in the US and compare these data with five previously published studies of IVLBCL.…”
mentioning
confidence: 99%